PCSP’s Diagonal Tie Connectors Thermal Bridges Impact on Energy Performance and Operational Cost: Case Study of a High-Rise Residential Building in Estonia - Kiil Martin; Käärid Martin-Sven; Klõšeiko Paul; Võsa Karl-Villem; Simson Raimo; Sarevet Henri; Thalfeldt Martin; Kurnitski Jarek (E3S Web of Conferences, 2020)
This study analyses the effect of air circulation around diagonal tie connectors in precast sandwich panels on heating energy demand, energy performance value and heating costs of a sample residential building. Dynamic simulations were performed using 4 different climatic boundary conditions: Estonian test reference year, Estonian 48-year weather dataset as well as data from Eastern Germany and Northern Finland. The results show that the effect of the thermal bridge is most noticeable in total room heating energy demand (increase of 10.3%), while the influence on energy performance value was 1.1%. The relative increase of total room heating energy demand was similar (7.0-10.3%) in all studied climatic regions.